2015
DOI: 10.1038/ncomms9265
|View full text |Cite
|
Sign up to set email alerts
|

Differential genomic imprinting regulates paracrine and autocrine roles of IGF2 in mouse adult neurogenesis

Abstract: Genomic imprinting is implicated in the control of gene dosage in neurogenic niches. Here we address the importance of Igf2 imprinting for murine adult neurogenesis in the subventricular zone (SVZ) and in the subgranular zone (SGZ) of the hippocampus in vivo. In the SVZ, paracrine IGF2 is a cerebrospinal fluid and endothelial-derived neurogenic factor requiring biallelic expression, with mutants having reduced activation of the stem cell pool and impaired olfactory bulb neurogenesis. In contrast, Igf2 is impri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 45 publications
1
91
0
Order By: Relevance
“…Genes in the Dlk1-Dio3 locus are highly expressed in the brain, an organ that was previously associated with complex parent-of-origin effects (Davies et al, 2005; Ferron et al, 2015; Perez et al, 2015; Sittig and Redei, 2014; Wilkinson et al, 2007; Xie et al, 2012). A recent report suggested that gain or loss of DNA methylation in the IG-DMR region may be regulated in a dynamic manner in the adult neurogenic niche (Ferron et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Genes in the Dlk1-Dio3 locus are highly expressed in the brain, an organ that was previously associated with complex parent-of-origin effects (Davies et al, 2005; Ferron et al, 2015; Perez et al, 2015; Sittig and Redei, 2014; Wilkinson et al, 2007; Xie et al, 2012). A recent report suggested that gain or loss of DNA methylation in the IG-DMR region may be regulated in a dynamic manner in the adult neurogenic niche (Ferron et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…IGF2 and IGF1 receptor (IGF1R) signalling are thus emerging as key, context-dependent regulators of stem cell self-renewal and the proliferation of early progenitor cell pools in normal tissue architectures 6264 , tumour tissues 59,60 and embryonic stem cell (ESC) cultures 65 . The properties of IGF2 in promoting stemness and tipping the balance between the stem/progenitor cell pool and differentiated progeny seems to be tightly connected with its role in cancer initiation and progression 57,59,60 .…”
Section: Epigenetic Mediatorsmentioning
confidence: 99%
“…Interestingly, this paracrine mode of DLK1 signaling requires derepression of its maternal allele to achieve biallelic expression in both astrocytes and NSCs. Similarly, derepression of the Igf2 maternal allele to achieve biallelic expression in the SVZ is also required for NSC self-renewal postnatally, suggesting a remarkable mechanism of transcriptional dosage control in adult neurogenesis through imprinting regulation (Ferrón et al 2015). In the SGZ, the maternally expressed CDKN1C facilitates the maintenance of NSC quiescence (Furutachi et al 2013), and in contrast to the SVZ, IGF2 is paternally expressed and operates in an autocrine manner to regulate NSC survival (Bracko et al 2012, Ferrón et al 2015).…”
Section: Imprinted Genes and Epigenetic Control Of Neural Developmentmentioning
confidence: 99%
“…IGF2, which promotes adult neurogenesis (Bracko et al 2012, Ferrón et al 2015), is downregulated in animals exhibiting depression-like behavior after chronic stress (Luo et al 2014). Remarkably, overexpression of Igf2 in the dentate gyrus reverses these behaviors, but whether this effect is dependent on adult neurogenesis remains to be tested.…”
Section: Functions Of Imprinted Genes In the Postnatal Brainmentioning
confidence: 99%